Care manager role for older multimorbid heart failure patients’ needs in relation to psychological distress and quality of life: a cross-sectional study - Gostoli, Sara; Subach, Regina; Guolo, Francesco; Bernardini, Francesco; Cammarata, Alessandra; Gigante, Graziano; Herbeck Belnap, Birgit; Della Riva, Diego; Urbinati, Stefano; Rafanelli, Chiara (Frontiers in Cardiovascular Medicine, 2024)
Background There are few studies investigating patients’ needs in healthcare focusing on disease severity and psychological characteristics of elderly heart failure (HF) patients with multimorbidity, specifically addressed by a care manager (CM). Aims To explore the role of a CM dealing with elderly multimorbid HF patients’ needs/preferences according to NYHA class, ejection fraction, psychological/psychosomatic distress and quality of life (QoL), utilizing a Blended Collaborative Care (BCC) approach (ESCAPE; Grant agreement No 945377). Methods Cue cards, self-reported questionnaires, and a semi-structured interview were used to collect data. Results Twenty-five Italian patients (mean age ± SD = 77.5 ± 6.68) were enrolled between June 2021 and March 2022. The most relevant patients’ needs to be addressed by a CM were: education (e.g., on medical comorbidities), individual treatment tailoring (e.g., higher number of appointments with cardiologists) and symptom monitoring. Conclusion The study highlights the importance of targeting HF patients’ needs according to psychological characteristics, whose healthcare requires person-centered care with CM assistance. In view of ESCAPE BCC intervention, a CM should consider specific patients’ needs of elderly multimorbid HF patients with psychological, psychosomatic distress, particularly somatization, and lower QoL to achieve a more personalized health care pathway. Study registration The «Evaluation of a patient-centred biopsychosocial blended collaborative care pathway for the treatment of multi-morbid elderly patients» (ESCAPE) study has been registered at the University of Göttingen Medical Centre (UMG Reg. No 02853) and the German Clinical Trials Register (DRKS00025120).